Indigenous self-determination in cryospheric science: The Inuit-led Sikumik Qaujimajjuti (“tools to know how the ice is”) program in Inuit Nunangat, Canada - Beaulieu, L.; Arreak, A.; Holwell, R.; Dicker, S.; Qamanirq, O.; Moorman, L.; Wilson, K.; Segal, R.; Crichton, S.; Bell, T. (Frontiers in Earth Science, 2023)
Inuit wellbeing, culture, and identity have long been tied to safe and dependable sea-ice access. Our Elders and experienced ice users recognize their accumulated wisdom and experience of safe ice travel must be shared and applied in new ways for the benefit of younger generations, particularly as ice becomes increasingly unpredictable. The Sikumik Qaujimajjuti program enables young Inuit scientists to learn and apply the tools and skills they need to create operational community-scale sea-ice maps. Our cross-cultural partnership approach develops geospatial and cartographic skills of young Inuit, while non-Indigenous partners provide mentorship, tools, and training. Our novel maps incorporate culturally relevant ice terminology, on-ice monitoring data and observations, and interpretations of ice features and travel conditions from near-real time optical and radar satellite imagery, grounded in Inuit Qaujimajatuqangit (IQ; knowledge and values) of sea-ice. The layers of data are integrated into a local GIS, enabling the creation of maps at spatial scales that reflect local and seasonal travel patterns, on a schedule consistent with local sea-ice dynamics and information needs. The maps are shared in venues and media preferred by our communities and are a trusted source of travel information because they are made by one of our own, using local language, experience, and IQ. Sikumik Qaujimajjuti illustrates the incredible potential of Indigenous self-determination in cryospheric science when the scientific merit of IQ is fully recognized, when Indigenous researchers are able to access technologies and training to apply their IQ, and when non-Indigenous partners mentor and support young Indigenous scientists.